2022
DOI: 10.1177/10600280221077158
|View full text |Cite
|
Sign up to set email alerts
|

Observed Apixaban Anti-Xa Levels in Obese Patients

Abstract: Background: Recent guidelines suggest that, for venous thromboembolism (VTE), standard doses of apixaban are appropriate in patients with body mass index (BMI) >40 kg/m2 or >120 kg. Atrial fibrillation (AF) is excluded from this recommendation. Objective: The goals of our study were to measure and describe anti-Xa levels of patients with a BMI ≥40 kg/m2 and/or a weight ≥120 kg with a clinical indication of AF or VTE who were treated with apixaban, and to determine whether BMI or weight are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Similarly, an observational cohort study measuring anti-Xa levels of AF or VTE patients with a BMI ≥40 kg/m 2 and/or a weight ≥120 kg who have treated with apixaban 5 mg or 2.5 mg bid, of 55 patients enrolled, 9% had peak and 6% had trough anti-Xa levels below the reference ranges. 22 Although body weight had a moderate, negative correlation with peak anti-Xa levels and a weak, inverse correlation with trough anti-Xa levels, the results showed that anti-Xa levels among obese patients are not substantially different from patients with normal BMI and weight.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, an observational cohort study measuring anti-Xa levels of AF or VTE patients with a BMI ≥40 kg/m 2 and/or a weight ≥120 kg who have treated with apixaban 5 mg or 2.5 mg bid, of 55 patients enrolled, 9% had peak and 6% had trough anti-Xa levels below the reference ranges. 22 Although body weight had a moderate, negative correlation with peak anti-Xa levels and a weak, inverse correlation with trough anti-Xa levels, the results showed that anti-Xa levels among obese patients are not substantially different from patients with normal BMI and weight.…”
Section: Resultsmentioning
confidence: 77%
“…An ambulatory assessment of anti-Xa level for obese adults and a team-based evaluation involving hematologists and, additionally, drug-level monitoring for underweight patients have been proposed as possible solutions [ 229 ]. Nevertheless, DOACs seem to be more effective and safer than OACs among all BMI patients [ 230 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational cohort study 37 was conducted in VTE and/or NVAF patients with a BMI >40 kg/m 2 and/or a weight >120 kg, treated with apixaban in the usual doses. Anti-Xa levels were routinely measured.…”
Section: Doacs For Vte Treatment and Secondary Prevention In Obese Pa...mentioning
confidence: 99%